Metastasis of soft tissue sarcomas in lymph node: A cytomorphological study. Issue 9 (24th May 2017) - Gandhi, Jahnavi; Mehta, Shailee; Patel, Trupti; Gami, Amisha; Shah, Majal; Jetly, Dhaval
Abstract : Background: Soft‐tissue sarcoma (STS) rarely metastasizes to lymph node compared to carcinoma. Fine‐needle aspiration cytology (FNAC) carries a pivotal role in diagnosis of metastatic tumor to lymph node. This study highlights the role of FNAC in diagnosis of STS metastasis to lymph node. Method: A retrospective study over a period by 4 years carried out. FNAC of enlarged lymph node was performed in patients with STS. Cytology smears were examined in conjunction with clinical details. Histopathology and Immunohistochemistry (IHC) were correlated in synchronous cases. Results: Out of 326 patients, 21 with STS had enlarged lymph nodes, of which 19 cases showed involvement (5.8%). Sixteen cases were metachronous and 3 cases showed synchronous involvement. Fifteen cases had regional lymph nodes while 4 cases had distal lymph node involvement. Head and neck and lower extremities were the most common primary sites of STS. Rhabdomyosarcoma was the most common sarcoma metastasing to the lymph nodes followed by synovial sarcoma, malignant peripheral nerve sheath tumor, and clear cell sarcoma. Other rare tumors included leiomyosarcoma, epitheloid sarcoma, liposarcoma, malignant fibrous histiocytoma, and Ewing's sarcoma/peripheral neuroectodermal tumor. We had a case of dermatofibrosarcoma protuberance (DFSP) of scalp with cervical lymph node metastasis. Very unusual about this case was its rare primary site and the rarer lymph node metastasis. Conclusion: FNAC plays an important role in the diagnosis of lymph node metastasis in cases of STS.